Plastik Sanatlar Alanında Seramik ve Cam Üzerine Yaklaşımlar 8 - Bozkurt, Emel; Savaş, Fulya; Biçici Çetinkaya, Pınar; Sert, İrem and Güngör, Memduha Candan and Karacalar, Şule and Gürgöze, Hüseyin and Yılmazer, Yunis and Akkalan, Yunus Emre and Çalışkan Güneş, Pınar and Aksakal, Agâh Barış Can and Yalçın, Burhan and Arda, Ergün and Yavaş, Yeşim (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-